Validation Of Multi-Domain Satisfaction Scales From The Well-Being Inventory On Ex-Servicemen From Indian Armed Forces - Shidganesh, Anirudh Shastri; Singh, Ram Manohar (Migration Letters, 2024)
This study evaluates the cross-cultural validity and reliability of the scales measuring multi-domain satisfaction from the Well-being Inventory. An online cross-sectional survey was conducted using convenience sampling to collect data from 412 Ex-Servicemen of the Indian armed forces. The confirmatory factor analysis results using robust maximum likelihood estimation on Mplus 8.1 provides acceptable model fit indices for the first-order six-factor model RMSEA= 0.03, SRMR =0.0[1]6, CFI = 0.96 and TLI = 0.96,. The average variance extracted for factors in the model ranges between 0.53 – 0.67. The construct reliability for sub-domains ranges between 0.80-0.93. The model shows acceptable discriminant and convergent validity using the Fornell-Larcker criterion and Heterotrait-Monotrait approach. The first order six-factor model shows good composite reliability having Omega = 0.91. The principal component analysis for sub-domains confirms the unidimensional factor structure of each sub-domain. Each sub-domain scale possesses adequate internal consistency reliability with Cronbach alpha ranging between 0.78 to 0.92. The results of Pearson’s correlation between each sub-domain and Satisfaction with Life Scale ranges between 0.36-0.58 with p<0.001, indicating a significant positive correlation. The comprehensive summated score shows a moderate positive correlation with SWLS (r = 0.60). The multi-domain scales are valid tools for comprehensive and segregate measurement of satisfaction for Ex-Servicemen from the Indian armed forces in work, finance, health, intimate partner relationship, parenting, and broader social domains of life.